Moving Bed Sequencing Batch Reactor: Optimization Of Operational Parameters For Nitrogen And 4-Chlorophenol Removal - Lim, Jun Wei (2013)
Moving bed sequencing batch reactor (MBSBR) which incorporates both suspended-growth and attached-growth biomasses in a single reactor has been widely used in wastewater treatment plants. Nevertheless, information on the treatment of nitrogen containing wastewater via MBSBR is still scarce. Thus, more attention from researchers to explore the potential of using MBSBR in biological nitrogen removal is needed. This study aimed to optimize the use of polyurethane (PU) foam cubes as a support media and to apply the optimum aeration strategy during the REACT phase in the MBSBR for the enhancement of nitrogen removal in low COOIN ratio wastewater. In addition, the effect of 4-chlorophenol (4-CP) on the simultaneous 4- CP and nitrogen removal in the MBSBR was also investigated. The MBSBR was initially packed with PU foam cubes of various sizes to determine the effect of support media size on nitrogen removal. Subsequently, the aeration strategy during the REACT phase was converted from continuous to intermittent aeration and the performance of both aeration strategies in removing nitrogen was compared. The attached-growth biomass from the PU foam cubes was also dried and later added into the MBSBR to assess the feasibility to be utilized as an alternative solid carbon source in enhancing the nitrogen removal.